The benefits and challenges of embedding specialist palliative care teams within homeless hostels to enhance support and learning: Perspectives from palliative care teams and hostel staff. (June 2021) - Armstrong, Megan; Shulman, Caroline; Hudson, Briony; Brophy, Niamh; Daley, Julian; Hewett, Nigel; Stone, Patrick
Background: People residing in UK homeless hostels experience extremely high rates of multi-morbidity, frailty and age-related conditions at a young age. However, they seldom receive palliative care with the burden of support falling to hostel staff. Aim: To evaluate a model embedding palliative specialists, trained as 'homelessness champions', into hostels for two half-days a month to provide support to staff and residents and facilitate a multidisciplinary approach to care. Design: An exploratory qualitative design. Setting/participants: Four homeless hostels in London, UK, including nine hostel managers/support staff and seven palliative care specialists (five nurses and two social workers). Results: Benefits to introducing the model included: developing partnership working between hostel staff and palliative care specialists, developing a holistic palliative ethos within the hostels and improving how hostel staff seek support and connect with local external services. Challenges to implementation included limited time and resources, and barriers related to primary care. Conclusion: This is the first evaluation of embedding palliative care specialists within homeless hostels. Inequity in health and social care access was highlighted with evidence of benefit of this additional support for both hostel staff and residents. Considering COVID-19, future research should explore remote ways of working including providing in-reach support to homelessness services from a range of services and organisations.